The Phenomena of Bogomilism in the Context of Hagiographic Literary Works - Angelovska-Panova, Maja (Studia Ceranea, 2022)
Hagiography represents a special literary genre, which primarily deals with the life of the Saint, also providing information on certain historical events. Taking into consideration the complexity of the genre, it is a common impression that the credibility of the historical narrative is debatable and it can oscillate from subjective to objective positions. Thus, the purpose of the article is to reconstruct certain aspects on Bogomilism as a medieval dualistic movement, having in mind the content of hagiographic literary works. In that respect, the focus will be concentrated on the issue whether and to what extent hagiographic literary works can be treated as a relevant source material. Especially if we suppose that the information related to Bogomils can be indirect, incidental, biased, or having a legendary character. Of course, where possible, comparisons will be made with the accounts from the relevant historical narratives. According to the chronological order several examples from the hagiographic literature will be taken, as: The Short Life of St. Clement, written by the Ohrid Archbishop Theophylact, The Life of Hilarion of Moglena, The Life of St. Sava, The Life of Theodosius of Trnovo as well as The Life of John Vladimir. Despite the difficulty in identifying the authenticity of the historical events, in our case concerning the Bogomilism, hagiographic texts still contain useful material about that how Bogomilism functioned in certain periods and what were the repercussion for the protagonists of the movement.